Effectiveness of Deep Breathing Relaxation Therapy on Reducing Hypertension Pain - Nurwijayanti, Andriyani Mustika; Aeni, Qurrotul; Anggraeni, Rina (Journal of Economics and Public Health, 2025)
Headache is a common complaint in hypertension sufferers. Pain management using deep breathing relaxation therapy can stimulate the body to release endogenous opioids, namely endorphins and enphekalins, which are useful for reducing pain. Likewise, music therapy can also reduce pain by distracting a person from the sensation of pain. The purpose of this study was to determine the difference in effectiveness of deep breathing relaxation therapy and music therapy in reducing hypertension pain in Pegandon Village, Pegandon District. This study used a quasi-experimental design with a pre-test post-test with a control group. The research instrument used a Numeric Rating Scale observation sheet. The study population was patients with hypertension. The total sample was 42 respondents, divided into 2 groups: 21 respondents with deep breathing relaxation therapy, and 21 respondents with control, selected using a purposive sampling technique. Data analysis used the Independent Sample T-Test. The results of the study obtained a p-value in the group after deep breathing relaxation therapy and the control group of 0.372>0.05, meaning there was no significant difference between the deep breathing relaxation therapy group and the control group in reducing hypertension pain in Pegandon Village, Pegandon District.